Climate change and financing adaptation by farmers in northern Nigeria - Terfa Williams Abraham; William M. Fonta (Financial Innovation, 2018)
This paper examines farmers' perceptions of their exposure to climate change in rural northern Nigeria. It also examines whether there is a significant relationship between the exposure of farmers to climate change and their need for financial access as an adaptation strategy. Questionnaires were administered to 320 respondents in rural communities in northern Nigeria. Descriptive analysis shows that rural farmers are affected by climate change through increased temperature, prolonged dry seasons, floods, and drought, which lead to low harvest and, in turn, low income. An estimate from a non-parametric test also shows a significant relationship between farmers' perceived exposure to climate change and their need for credit. Although the Spearman correlation results show a 63% association between exposure to climate change and the need for finance, 96% of those seeking credit to mitigate these impacts would be unable to do so due to financial exclusiveness. The paper recommends that the Central Bank of Nigeria should ensure that microfinance institutions refocus their products/services to those who need them the most in order to enhance access to financial resources and enable farmers to build resilience that will maximize post-harvest gains. Lastly, considering that climate change is a global phenomenon with local effects, perhaps the international community could support lending to smallholder farmers through central banks by insuring the loans that banks give to farmers towards financing climate change adaptation strategies.
Keywords: 650; Rural households; Farm income; Climate change; Financial inclusion